INTEGRATION OF LOCAL AND NATIONAL HISTORY AS A HOLISTIC APPROACH IN HISTORY LEARNING IN HIGH SCHOOL: INTEGRASI SEJARAH LOKAL DAN NASIONAL SEBAGAI PENDEKATAN HOLISTIK DALAM PEMBELAJARAN SEJARAH DI SMA - miskawi; Maulana Yusuf Arrasuly; Djono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
History education at the high school level has a strategic role in building historical awareness, national identity, and student character. This article discusses the importance of integrating local and national history as a holistic approach to history learning to create relevant, meaningful, and inclusive learning. Using a descriptive qualitative method based on literature studies, this study identifies the role of local history as a complement to the national narrative, as well as the challenges faced in its implementation, such as curriculum limitations, lack of supporting resources, and lack of teacher training. The resource-based learning model and the environmental approach as a history laboratory are effective strategies in supporting this integration. The results of the study show that the integration of local and national history can enrich history learning, strengthen students' awareness of local and national identity, and support the development of critical and historical thinking skills. This integration not only improves the quality of history learning but also contributes to the formation of a critical, caring, and responsible young generation.